PENGUATAN KELAS INKLUSI BERBASIS KURIKULUM MERDEKA BAGI GURU PAUD DI WILAYAH KABUPATEN SEMARANG - Diana, Diana; Fadhilah, Fathin Farah; Tasu’ah, Neneng; Hasjiandito, Akaat; Wahyu Arta, Rama; Af'idah, Nabila Zakiyyatul; Haryanti, Vita (LPPI UMN AL WASHLIYAH, 2024)
This community service aims to strengthen Early Childhood Education (ECE) teachers in the Semarang Regency area so they can manage learning activities based on the independent curriculum in inclusive classes. The methods used in this community service activity are in-training and on-training, divided into three stages. The in-training activities were carried out at the Semarang Regency Office, and the on-training was carried out using the Zoom meeting mode and LMS. The targets in this activity are representatives of ECE teachers representing IGTKI, supervisors, and supervisors in each sub-district of Semarang Regency, with a total of 28 people. The results of this service are likely successful, as indicated by an increase in teachers' knowledge, skills, and attitudes toward implementing inclusive education based on the independent curriculum. Teachers can design play activities that can support children's growth and development according to their needs. Improving the implementation of inclusive classes based on the independent curriculum means that teachers can modify the curriculum and collaborate with various parties such as doctors, psychologists and therapists.